2019
DOI: 10.1017/s1368980018004007
|View full text |Cite
|
Sign up to set email alerts
|

Social and economic influences on infant and child feeding practices in a Marshallese community

Abstract: ObjectiveThe present study aimed to examine the key influences on infant and child feeding practices among a Marshallese community at each social ecological level. It is the first study to examine the key influences on infant and child feeding practices with Marshallese immigrant women in the USA and helps fill a gap in the previous literature that has included other immigrant women.DesignCommunity-based participatory research design with twenty-seven participants taking part in four qualitative focus groups.S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 49 publications
(61 reference statements)
0
8
0
Order By: Relevance
“…Second, participants described gender breastfeeding preference deriving from a desire to not see their female infants become upset when weaning from the breast, whereas with male infants, this was not viewed the same. Previous research with Marshallese mothers identified infant-and/or child-led feeding [34,37]. However, this is the first study to identify a gender preference in infant feeding decision making among Marshallese or other Pacific Islander women.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Second, participants described gender breastfeeding preference deriving from a desire to not see their female infants become upset when weaning from the breast, whereas with male infants, this was not viewed the same. Previous research with Marshallese mothers identified infant-and/or child-led feeding [34,37]. However, this is the first study to identify a gender preference in infant feeding decision making among Marshallese or other Pacific Islander women.…”
Section: Discussionmentioning
confidence: 83%
“…Arkansas has the largest population of Marshallese living in the continental US (~14,000 people) [26][27][28][29][30]. Marshallese culture is matriarchal and collectivist, with immense value placed on motherhood [31][32][33][34][35][36]. Now that the Marshallese community has migrated to the US, their maternal culture has been disrupted, affecting reproductive life planning, pregnancy, birth, and especially their infant feeding behavior and experiences [31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This level of food insecurity among pregnant women is much higher than it has been documented in other populations [ 30 , 31 , 32 ]. The previous qualitative literature with the Marshallese in Arkansas has identified a strong desire for both healthy and traditional foods and financial barriers to obtaining them [ 19 , 33 ]. This is the first article to document this qualitative concern among pregnant Marshallese and the first study among pregnant Marshallese to document the high level of food insecurity risk using Hager et al’s 2-item screening measure [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…This type of research is uniquely suited for engaging indigenous and/or immigrant populations. As part of the CBPR collaborative, the research team has spent the past six years meeting with Marshallese community members to determine and prioritize the community’s primary health concerns [ 17 , 18 , 19 , 20 , 21 ]. Maternal health was identified as a top priority.…”
Section: Introductionmentioning
confidence: 99%